Blockchain Technology for Cashless Investments and Transactions in Digital Era With SWOT Approach - Yusup, Muhamad; Sukmawati, Eva; Ramadhan, Rezki; Suhaepi, Muhamad Iip; Zebua, Selamat; Amallia, Naila (IAIC Bangun Bangsa, 2022)
One of the most visible information technologies in today's digital age is transaction and investment technology, where users or the public are facilitated in transactions by no longer using cash. Users also feel safer because they do not need to carry cash. Moreover, the current digital era makes it easy for users or the public to invest anywhere and anytime without disrupting other businesses. Blockchain technology can be used as an alternative to non-payment transactions or commonly known as cashless transactions. Blockchain technology can also be used as an investment in electronic money. The methodology used to provide an overview and evaluate the benefits of blockchain as an alternative to digital payment and investment activities in the cryptocurrency industry uses a SWOT approach. Based on the SWOT approach that has been taken, it can be concluded that with internationally recognized safeguards of confidentiality and the ease of conducting investment transactions and activities without payment, the Weaknesses and threats can be controlled for more investors to enter the world of electronic money.